Etnomatematika Melalui Simbol dan Komunikasi Nonverbal dalam Tradisi Marosok di Minangkabau - Rani Rahim (Universitas Batanghari Jambi, 2023)
Studies that examine mathematical ideas or practices in various cultural activities are known as ethnomathematics. Ethnomathematics studies mathematical ideas in various cultural activities carried out by ethnic, social or professional groups. This research was conducted as part of the exploration in the Marosok trade tradition by the Minangkabau tribe in West Sumatra. This study aims to reveal the practice of mathematics through symbols and gestures contained in buying and selling transactions through the Marosok tradition in Minangkabau. The Marosok buying and selling tradition is the tradition of shaking hands